The Dynamics of Strategic Collaboration Between the Public and Private Sectors in Driving Sustainable Innovation in the Era of Digital Transformation - Ade Suhara; Hendra Sugiarto; Doddy Nur Pratomo (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study explores the dynamics of strategic collaboration between the public and private sectors in driving sustainable innovation amid digital transformation. It addresses the challenges faced by these sectors in aligning goals and integrating digital technologies effectively. Using a library research method, the study analyzes secondary data from books, journals, and case studies related to public-private collaboration, digital transformation, and sustainable innovation. The findings reveal that successful collaborations require clear governance, shared objectives, and effective use of digital technologies. However, challenges such as regulatory misalignment and trust issues must be overcome. Ultimately, fostering these collaborations can drive more sustainable, innovative solutions for both economic and societal benefit in the digital age.